Self-determination among learners with developmental disabilities - Tan, Jacqueline Uy; Adorio, Mercedes P. (2012)
The study describes the presence of opportunities for learners with developmental disabilities that pertain to the different components of self-determination, and the trends supporting the increase in opportunities of these learners. It also explored the views that parents hold about the importance of independence in the seven areas of life (personal care, community involvement, recreational and leisure activities, independent living, supported employment, marriage and family, and managing finances). The results of the study revealed that a positive relationship exists between parents' and teachers' perception of learners' level of ability and the opportunities that are provided for these learners to practice skills that lead to self-determination. Parents who have a positive and optimistic view of their children's capacity to be independent tend to encourage engagement in learning through opportunities to practice skills on a daily basis. It is thus recommended that learners with developmental disabilities be given more opportunities to engage in life experiences that foster the development of self-determination. Teachers are also encouraged to provide opportunities that will challenge their students optimally and help develop essential skills. Finally, parents should also complement the school initiatives by increasing the emphasis on the development of self-determination skills in the home.
Keywords: Autonomy (Psychology); Developmental disabilities